Metrics Based on a Risk-Driven Approach to Assess Communication, Cooperation and Coordination in Global Software Development Teams (2020)
The success of Global Software Development (GSD) depends largely on how geographically dispersed project management and teamwork efforts are communicated, cooperated and coordinated (3Cs). From a literature analysis, some works were found where risks and metrics for DGS projects are proposed, but it was evidenced that some risks are not described in detail, they are ambiguous and hard to understand, which makes it difficult to know which category they belong to. In addition, it is necessary to classify risks in a less-subjective way, which allows to improve their understanding and thus define and apply measurement tools to obtain the impact magnitude of mentioned risks, and generate some indicators for support decision-making in DGS teams. In this article, 37 risks for the communication, cooperation and coordination in the DGS are proposed, as a result of the comparison and integration of identified risks in the literature. A set of metrics defined with the application of the Goal Question Metric (GQM) paradigm is also presented, organized according to these questions: What does it measure? Where the attribute to be measured is established; How to measure it? Where the metric is formulated through the following elements: description, type, scale and calculation function. Through the focus group technique, its completeness, relevance, clarity, precision, and ease of use were evaluated. The proposed metrics could be useful for organizations, teams, projects, and consultants operating in DGS contexts.